2021
DOI: 10.1136/bmj.m4931
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papillomavirus vaccination and serious adverse events in South Korean adolescent girls: nationwide cohort study

Abstract: Objective To evaluate the association between human papillomavirus (HPV) vaccination and serious adverse events in adolescent girls in South Korea. Design Cohort study. Setting A large linked database created by linking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
0
14
0
8
Order By: Relevance
“…Most of the parents had the desire to have their daughters vaccinated so long as the vaccination was to prevent the girls from getting cervical cancer later in life [52]. These effects can be mitigated by proper information [58], such as the success rate of promotion campaign targeting the community and leaders, in well bounded community as the Kenyan one, the community can be led by the village elders who will take up this role [53].…”
Section: Integration With Prior Work Implications Transferability and Contribution To The Fieldmentioning
confidence: 99%
“…Most of the parents had the desire to have their daughters vaccinated so long as the vaccination was to prevent the girls from getting cervical cancer later in life [52]. These effects can be mitigated by proper information [58], such as the success rate of promotion campaign targeting the community and leaders, in well bounded community as the Kenyan one, the community can be led by the village elders who will take up this role [53].…”
Section: Integration With Prior Work Implications Transferability and Contribution To The Fieldmentioning
confidence: 99%
“…Concerning Human Papillomavirus (HPV), the literature is more consistent. Several systematic reviews found an association between HPV vaccination and thyroid disease (66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the safety of the HPV vaccine, no associations with multiple sclerosis, other disorders of the central nervous system, demyelinating disorders, Guillain-Barré syndrome, neurological diseases, venous thromboembolism, and autoimmune diseases have been revealed in observational studies and randomized clinical studies [ 50 51 52 53 ]. In addition, in a recently published registry-based study on 11–14-year-old Korean girls, 33 serious complications, including Hashimoto's thyroiditis, rheumatoid arthritis, and malignant headache, were demonstrated to not be associated with HPV vaccination [ 54 ].…”
Section: Discussionmentioning
confidence: 99%